2020
DOI: 10.1093/hmg/ddaa058
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study finds genetic variants associated with neck or shoulder pain in UK Biobank

Abstract: Background Common types of musculoskeletal conditions include pain in the neck and shoulder areas. This study seeks to identify the genetic variants associated with neck or shoulder pain based on a genome-wide association approach using 203 309 subjects from the UK Biobank cohort and look for replication evidence from the Generation Scotland: Scottish Family Health Study (GS:SFHS) and TwinsUK. Methods A genome-wide associatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Finally, genetic factors underlying chronic pain and psychiatric co-morbidity (e.g., depression and neuroticism) are known to be shared[62]. However, previous GWAS on chronic pain[29, 63, 64], depression[65] and neuroticism[66] have failed to detect an association with COMT . Thus, if there is a role of COMT in CWP, it is likely minimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, genetic factors underlying chronic pain and psychiatric co-morbidity (e.g., depression and neuroticism) are known to be shared[62]. However, previous GWAS on chronic pain[29, 63, 64], depression[65] and neuroticism[66] have failed to detect an association with COMT . Thus, if there is a role of COMT in CWP, it is likely minimal.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous GWAS on chronic pain [29,63,64], depression [65] and neuroticism [66] have failed to detect an association with COMT. Thus, if there is a role of COMT in CWP, it is likely minimal.…”
Section: Cwp Shares Genetic Components With Bmi Depression Age At Fmentioning
confidence: 97%
“…We used two self-administered pain sensitivity measurements, the PSQ and CPT, and established that they could be reliable phenotypes for evaluating the genetic architecture of pain sensitivity. PSQ score and CPT duration have been previously shown to be only moderately phenotypically correlated (r = -0.22 [-0.27, -0.17]) [8]. The PSQ is a pain intensity rating of imagined painful situations occurring in daily life, whereas the CPT directly measures pain tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the number of genome-wide association studies (GWAS) on pain phenotypes is still very limited. The largest pain GWAS have been performed in the UK Biobank and 23andMe, Inc. cohorts for chronic pain [5] [6], knee pain [7], neck and shoulder pain [8], and migraine [9] [10]. These studies have identified dozens of putative causal genes, which are primarily expressed within brain tissues and have been implicated in neurogenesis, neuronal development, neural connectivity, and cell-cycle processes.…”
Section: Introductionmentioning
confidence: 99%
“…The SIS impingent hypothesis postulated a pathophysiological mechanism, different shoulder joint structures producing mechanical conflicts ( Garving et al 2017 ). A Genome-wide Association Study (GWAS) was recently performed to identify the genetic variants associated with neck or shoulder pain in the UK Biobank cohort, and three genetic loci were identified associated with neck or shoulder pain, such as rs2049604 in FOXP2 gene and rs62053992 in LINC01572 gene ( Meng et al 2020 ). However, the molecular mechanisms of SIS are rarely studied and the genetic pathogenesis of SIS is still unclear.…”
mentioning
confidence: 99%